A Translation of Directive Utterance on The Hunger Game Novel and Its Translation - Noorsita, Wida M; , Dr. Dwi Haryanti, M.Hum; , Drs. Sigit Haryanto, M.Hum (2016)
The objectives of this study are to identify the strategy of translation of directive utterance in the Text of The Hunger Game's Novel, and to describe the accurateness of translation on the directive utterances of The Hunger Game's Novel and its translation.The research is qualitative research. The object of the study is the directive utterances in the novel of The Hunger Game written by Suzanne Collins and its translation. The data source is The Hunger Game novel written by Suzanne Collins. The method of collecting data is documentation, with the steps: reading the novel, signing the directive utterances such as strategy of translation, coding the data in the novel, classifying the sentence based on the type of sentence and comparing the structure and the meaning of the novel. The result of the study shows that there are three directive utterances in The Hunger Game's Novel, those are: command, request and suggestion. Command directive utterance has five strategies, they are: deletion, addition, level shift, category shift, and adoption. Request directive utterance has also five strategies , they are: deletion, addition, level shift, structure shift, and adaptation, and suggestion directive utterance has two strategies, deletion and structural shift. The second findings shows that translation can be classified into accurate and less accurate. On this research there is no classification for inaccurate because the translator translates the novel with the closer meaning of the source to get the right meaning based on the story, this is happened only in the translation that is accurate and less accurate.